Mahdiism and Political Movement (Critical Study on Hadith of Mahdawiyah) - Muhammad Rikza Muqtada (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Believing in the presence of Imam al-Mahdi (called by Mahdiism) becomes an important part in the majority of Islamic theology. On the other hand Mahdiism always present in the crisis context that hit the depressed group, such as politic, economic, social and cultural. Therefore, mahdiism have double-faced in its presence, between religious movements and political movement to recapture the glory of Moslem ever achieved. Religion is a frame of ideology that legitimate and effective in political movement mission. This movement always complete with its ideology and its foundations of legitimacy. Mahdiism ideology in Islam is framed through hadith texts of mahdawiyah. These hadith is always related to the utopian hopes for the struggle (jihad) spirit. By Mahdiism, Islam as a religion has been converted into a religious political movement. Keyword: mahdiisme, hadis of mahdawiyah, religious political movement